1992
DOI: 10.1073/pnas.89.19.8976
|View full text |Cite
|
Sign up to set email alerts
|

Inositol polyphosphate receptor and clathrin assembly protein AP-2 are related proteins that form potassium-selective ion channels in planar lipid bilayers.

Abstract: Inositol polyphosphate receptor and clathrin assembly protein AP-2 are related proteins that form potassium-selective ion channels in planar lipid bilayers (receptor-mediated Clathrin-coated vesicles similar to fraction D described by Keen et al. (11) were prepared from three or four whole bovine brains.Clathrin and AP-2 were partially purified from the coated vesicles essentially as described by Keen et al. (11). Briefly, coated vesicles (1.5 g of protein) were extracted with 0.5 M Tris Cl (200 ml) in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

1994
1994
2001
2001

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(26 citation statements)
references
References 35 publications
1
25
0
Order By: Relevance
“…Previously Theibert et al [12] have described protein complexes occurring in brain tissue which bind Ins-P4 and with similar affinity Ins-Ps. One of these proteins displays K + channel activity [13]. The recently reported 104 kDa protein with Ins-P4 binding activity found in pig platelets [14] suggests the possibility that in non-brain, peripheral tissue Ins-P4 acts via some other Ins-P4 receptor proteins.…”
Section: Resultsmentioning
confidence: 97%
“…Previously Theibert et al [12] have described protein complexes occurring in brain tissue which bind Ins-P4 and with similar affinity Ins-Ps. One of these proteins displays K + channel activity [13]. The recently reported 104 kDa protein with Ins-P4 binding activity found in pig platelets [14] suggests the possibility that in non-brain, peripheral tissue Ins-P4 acts via some other Ins-P4 receptor proteins.…”
Section: Resultsmentioning
confidence: 97%
“…The role of amphiphysin-1 in clathrin-mediated endocytosis during synaptic vesicle reformation involves interactions with synaptojanin-1 (an inositol-polyphosphate 5-phosphatase), clathrin, and AP-2 (28,(41)(42)(43)(44)(45)(46). Interestingly, AP-2 has been characterized in vitro as an IP 6 -binding protein (47)(48)(49), and IP 6 alters the in vitro binding of AP-2 to synaptotagmin (50). Based on these reports, it was possible that scRvs167 and scRvs161 might have some function in the IP pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Partial amino acid sequencing of one protein has revealed that it is clathrin assembly protein 2 (AP-2), which is possibly an essential protein in the endocytotic or recycling pathway of all cells (17)(18)(19)(20) (18) is 120 nM. Dependence of the InsP X binding on the salt concentration in the assay system seems to account for this difference.…”
Section: Discussionmentioning
confidence: 99%
“…Several proteins involved in intracellular vesicular transport have been identified as InsP 6 -binding proteins. A clathrin assembly protein, AP-2 (17)(18)(19)(20), may be an essential protein in the endocytotic recycling pathway of all cells (21). Binding of InsP 6 inhibits the clathrin assembly me-diated by AP-2 (22) and AP-3, a synapse-specific clathrin assembly protein (23,24).…”
mentioning
confidence: 99%